Diseño de un sistema de gestión de almacenamiento aplicando las herramientas de lean manufacturing en el área de almacén de repuestos de la empresa POLYBOL S.A.S. (2024)
The purpose of the degree project was to determine how Lean Manufacturing tools can improve the production in the spare parts warehouse area of the company Polybol S.A.S., having as root cause the lack of inventory control, deficiency in the organization system of the area. The company is located in the industrial zone of Mamonal and is dedicated to the manufacture and commercialization of flexible plastic packaging.